Impact of System Quality, Information Quality, and Service Quality on the Benefits of Hospital Management Information System (HMIS): A Case Study at PGI Cikini Hospital, Jakarta - Panangian, Frengki; Hidayat, R Taufik (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
A hospital is a professional healthcare institution where services are provided by doctors, nurses, and other healthcare professionals. To carry out its tasks and functions, a hospital must be able to finance its operations. One way of achieving this is through the Hospital Management Information System (HMIS). The Hospital Management Information System (HMIS) exists because it offers benefits that can be achieved by using information systems. This study aims to examine the impact of system quality, information quality, and service quality on the hospital management information system at PGI Cikini Hospital in Jakarta. The research method used in this study is a survey, with a sample of 120 people. Data analysis was conducted using simple regression and multiple regression analysis between independent and dependent variables. The results of the study indicate a positive impact of system quality, information quality, and service quality on the hospital management information system at PGI Cikini Hospital in Jakarta. The findings show a combined effect of system quality, information quality, and service quality on the benefits of the Hospital Management Information System (HMIS) at PGI Cikini Hospital in Jakarta. Based on these findings, this study concludes that the benefits of the Hospital Management Information System (HMIS) at PGI Cikini Hospital will increase as the quality of the system, information, and services improve.